Female preachers and the public discourse on Islam in Malaysia - Ismail, Norbani (International Institute of Islamic Thought (IIIT), 2016)
This paper explores Malaysia’s activist female preachers (pendakwah) by highlighting the religious authority and leadership in preaching that they have attained due to their firm grounding in Islam’s fundamental sources and Arabic. I analyze their recorded online lectures, radio talks, and interviews to identify their common preaching styles and highlighted themes. The study finds that their highest objective is to help create a sound moral and ethical society via the fulfillment of moral and religious obligations. To that end, they deal primarily with spiritual development and family management issues, as well as draw spiritual and religious conclusions from important historical events. The paper concludes that they keep their activism within the confines of expected social norms and the bureaucracy of religious authority. By adhering to social and religious orthodoxy, they continue to gain authority and trust from both the established religious authorities and the public.